Variability in fatty acid composition in hemp (Cannabis Sativa L.) seeds depending on soil conditions. - Kotsiou, Michaela (My University, 2025)
Hemp (Cannabis Sativa L.) belongs to the Cannabaceae family and the Cannabis genus. Depending on its use Cannabis is categorized into two groups: marijuana and hemp. Marijuana is mostly used for recreational purposes because of its intoxicating characteristics, although it may also be used for medicinal purposes. Hemp, on the other hand, is used for medicinal purposes, fiber, and seeds. Hemp seeds are the fruit of Cannabis Sativa L. The whole hemp seeds consist of 25–35% lipids, 20–25% protein, 20–30% carbohydrates, and 10-15% insoluble fibers and minerals. The high concentration of polyunsaturated fatty acids (PUFAs) in hemp seeds is mostly responsible for their benefits on human health. Hemp seed oil does not have psychotic effects but instead displays health-beneficial activity due to its ideal ratio of n-6 linoleic acid and n-3 linoleic acid (3:1) which is recommended in a healthy diet. The aim of the work is to study the effects that different soil conditions, such as processing with Arbuscular Mycorrhizal Fungi (AMF) and glyphosate residues, have on the lipid content and the fatty acid composition of hemp seeds. For this reason, four different soil types were used for the cultivation of the plants: control soil, control soil treated with mycorrhizal fungi, soil with glyphosate residues, and soil with glyphosate residues treated with mycorrhizal fungi. The lipids were first extracted in the form of oil from the hemp seeds using chloroform and methanol. After the extraction, the oil was methylated and analyzed using gas chromatography paired with a flame ionization detector (GC-FID). The results of the study indicated that the total lipid content increased in the samples that were treated with mycorrhizal fungi. The main fatty acids that were found in all the samples were palmitic acid (~5%), stearic acid (~2%), oleic acid (7-8%), linoleic acid (~50%), γ-linoleic acid (~5%), and α-linoleic acid (~20%). There was also a statistically significant difference (p<0.05) between the four different soil conditions in terms of the total lipid content and the sums of saturated fatty acids (SFAs), polyunsaturated fatty acids (PUFAs), and n-3 fatty acids. In conclusion, the treatment of the plants with mycorrhizal fungi increased the total lipid content but at the same time decreased the sums of polyunsaturated fatty acids and n-3 fatty acids.
Keywords: Keywords: Hemp, Total lipid content, Fatty acids, Lipid extraction, GC-FID, n-3 to n-6 ratio.